Positive mindset and exercise capacity in school-aged children and adolescents with congenital heart disease - Curran, Tracy; Losi, Rachel; Pymm, Jennifer; O’Neill, Julie Ann; Goveia, Nicole; Flanagan, Allison; Jakkam, Rajeshwari; Hansen, Katherine; Gauvreau, Kimberlee; Gauthier, Naomi (Frontiers in Pediatrics, 2023)
Introduction Patients with congenital heart disease (CHD) have variable degrees of peak oxygen consumption (VO2) that can be improved with supervised fitness training. The ability to exercise is affected by anatomy, hemodynamics, and motivation. Motivation is in part related to mindset, or personal attitudes and beliefs, and a more positive mindset around exercise has been associated with better outcomes. It is unknown whether variations in measured peak VO2 in patients with CHD are related to having a positive mindset. Methods Patient's ages 8–17 years with CHD were administered quality of life and physical activity questionnaires at the time of their routine cardiopulmonary exercise test. Those with severe hemodynamic burden were excluded. Patients were grouped based on disease classification. Mindset was evaluated via validated questionnaires including a PROMIS Meaning and Purpose (MaP) survey and an Anxiety survey. Pearson correlation coefficients were calculated to estimate the magnitude of the association between percent predicted peak oxygen consumption (pppVO2) and questionnaire scores overall and within CHD subgroups. Results Eighty-five patients participated; median age was 14.7 years, 53% were female, 66% had complex CHD, 20% had simple CHD, and 14% had single ventricle heart disease. Mean MaP scores were significantly lower in all CHD groups compared to population norms (p < 0.001). As a group, MaP scores were positively associated with the amount of reported physical activity (p = 0.017). In patients with simple CHD, MaP scores were positively associated with pppVO2 (p = 0.015). The association was even stronger for MaP:Anxiety, with worse ratios associated with lower pppVO2 (p = 0.005). Patients with complex and single ventricle CHD did not show a similar association. Conclusions Patients with CHD, regardless of severity, had lower meaning and purpose scores than the general population, and these scores were associated with amount of reported physical activity. In the simple CHD subset, having a more positive mindset was associated with higher peak VO2 and a more negative mindset with lower peak VO2. This relationship was not seen with more significant CHD. While underlying CHD diagnoses are not modifiable, mindset and peak VO2 are, and consideration should be given to measuring both as each may be a target for intervention.